Labor and welfare impacts of a large-scale livelihoods program: Quasi-experimental evidence from India - Pandey, Vivek; Gupta, Abhishek; Gupta, Shivani (World Bank, 2019)
Improving the livelihoods of poor households and transitioning more women back to the labor force is a major challenge in South Asia. Self-employment promoted through women's groups has often been cited as a promising intervention towards this end. However, the evidence on the impact of such programs on household income and labor outcomes is limited, especially for government programs like the National Rural Livelihoods Mission in India. This study aims to provide empirical evidence on the welfare impacts of an "intensive approach" adopted under this program. The data for the study come from 4,316 household surveys in 727 villages. The study uses matching methods with the population and socioeconomic census, as well as an instrumental variable approach to construct a retrospective control group. The analysis finds that the program has been able to achieve its primary objective of improving livelihoods by transitioning more women into work. The program has also expanded access to credit, increased the proportion of savings, and reduced interest rates on credit for rural households. This is the first study to estimate the annual income effects of a government-run rural livelihoods program in India, and it shows significant increases in median income across the sample. The results for 30th, 40th, and 75th percentiles are also large and significant. However, the study did not find significant average treatment effects for income. Contrary to previous studies, this study finds weaker impacts on assets, except for livestock.